2007
DOI: 10.1128/jcm.00013-07
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chlamydia trachomatis and Neisseria gonorrhoeae Infections in North American Women by Testing SurePath Liquid-Based Pap Specimens in APTIMA Assays

Abstract: The APTIMA COMBO 2 assay, which detects and amplifies rRNA from Chlamydia trachomatis and/or Neisseria gonorrhoeae, is approved for use on ThinPrep liquid-based Pap test specimens. The objective was to determine the clinical utility of the APTIMA assays (APTIMA COMBO 2 assay, APTIMA CT assay for Chlamydia trachomatis, and APTIMA GC assay for Neisseria gonorrhoeae) for screening women during their annual Pap exam, using SurePath liquid-based Pap test specimens. Two cervical samples were collected from 1,615 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…Seven of these studies met our full inclusion and exclusion criteria: original study on Chlamydia screening among women; and vaginal swab or endocervical swab used for AC2 testing. 15-21 …”
Section: Methodsmentioning
confidence: 99%
“…Seven of these studies met our full inclusion and exclusion criteria: original study on Chlamydia screening among women; and vaginal swab or endocervical swab used for AC2 testing. 15-21 …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that differences in analytical sensitivity of nucleic acid amplification tests (6) and inhibitors of DNA amplification (2, 3) may account for lower sensitivities in the AMP and PT assays. The sensitivity of AC2 for C. trachomatis in SurePath L-Pap samples in the present study was equal to that for testing of a CS (97.1%) and higher than those observed previously in a multicenter study (5) and two validation studies (4, 7) (Table 1).…”
Section: Discussionmentioning
confidence: 36%
“…A chlamydia test may be easily performed during a pelvic examination by obtaining a swab specimen of the endocervix or vagina, or by using the residual liquid from a liquid-based cytology specimen obtained during cervical cancer screening. 5,16 If a pelvic examination is not performed, then a chlamydia test can be done using a self-collected vaginal swab or a urine specimen. 5,17 However, these opportunities were missed at most visits to outpatient clinics.…”
Section: Discussionmentioning
confidence: 99%
“…1 More than one half of these reported cases were in women aged [15][16][17][18][19][20][21][22][23][24][25] years. Yet this rate likely underestimates the true burden of chlamydia, because of insufficient screening and reporting.…”
mentioning
confidence: 99%